EFFECTIVENESS OF VILLAGE FUND USE ON PHYSICAL AND NON-PHYSICAL INFRASTRUCTURE DEVELOPMENT IN ENAROTALI VILLAGE, PANIAI REGENCY - Mote, Evikson; Devy Pramudiana, Ika; Widyawati (International Journal of Multidisciplinary Reseach, 2026)
This study aims to evaluate the effectiveness of Village Fund utilization for physical and non-physical infrastructure development in Enarotali Village, East Paniai District, Paniai Regency, and to uncover the influencing factors in order to strengthen transparent and accountable village financial governance. The research approach used is qualitative with analytical descriptive method, where data is collected through participatory observation, in-depth interviews with key informants such as the Village Head and community leaders, and documentation of the 2023-2025 Village Budget realization report. The results of the study indicate that the use of Village Funds in Enarotali Village in the implementation of physical and non-physical infrastructure development is classified as effective due to the continuity of well-planned work programs. Quantitatively, the realization of the 2023-2025 physical budget ranges from 70% to 73% (Rp477 million - Rp548 million) which is focused on road construction to Mount Pogei tourist area and drainage maintenance. Meanwhile, the realization of the non-physical budget ranged from 10% to 11% (Rp63 million – Rp82 million) allocated for technical guidance on village tourism development, entrepreneurship training, and strengthening the capacity of BUMDes. This effectiveness is supported by four main indicators: the achievement of welfare-oriented goals, thorough planning through the Musrenbangdes forum, the preparation of appropriate programs in accordance with Law Number 6 of 2014, and a monitoring system involving the community and district auditors. Despite challenges such as geographical constraints and delays in disbursement of funds from the local government, which often only arrived at the end of the year, the village government was able to maintain synchronization between the development of physical infrastructure and improving the quality of human resources. This success proves that good coordination between participatory planning and strict monitoring is the main key to minimizing budget irregularities while ensuring maximum benefits for the community in remote areas of Enarotali Village.